Influence of nozzle structure on the combustion performance of a graphitic hydrogen-chlorine synthesis combustor. (25th January 2023) - Li, Ming; Wang, Yuncong; Cheng, Hui; Jiang, Yan; Zhang, Chunwei
Highlights: The combustion of hydrogen and chlorine in a synthesis combustor is analyzed. The mounting height of nozzle has the greatest influence on combustor performance. Small jet hole diameter promotes heat exchange and increases HCl production. Higher gas flow velocity is required for recirculation zone. Abstract: The growing semiconductor sector is driving up demand for high-purity gas-phase HCl. Large combustion zones and low HCl concentrations are problems for HCl manufacturing systems. Based on the realizable k-ε model, the eddy breakup combustion model, and the participating media radiation model, the computational fluid dynamics simulation was used as the primary means in this study. The influence of four structural factors, nozzle jet hole diameter, jet angle, and opening angle—another is nozzle mounting height, on the combustion effect of the synthesis combustor was investigated. The extent of the high-temperature zone in the synthesis combustor and the purity of the hydrogen chlorine at the outlet were used as the main evaluation criteria. The results of numerical simulations demonstrate that the better the gas mixing and combustion in the combustor, the lower the nozzle mounting height should be. Small nozzle diameters and large nozzle jet angle increase gas flow velocity in the recirculation zone close to the inner wall of the combustor. Additionally, the recirculation zone will appear in the combustor as a result of the nozzle's presence. The area of the high-temperature zone within the combustor decreases as internal gas velocity increases. On the other hand, the recirculation gas flow is not significantly impacted by the angle at the condition that the jet holes open. The results of the investigation provide a reference for the design of the miniaturization of the combustor in the non-premixed combustion synthesis of gases process.